On-line Distance Learning for improving socioeconomic status of rural farming community in Sri Lanka - Vidanapathirana, Nisansala Priyadarshani; Hirimburegama, Kshanika; Coomaraswamy, Uma (My University, 2012)
Agriculture is the mainstay of the rural sector that occupies almost 75% of the total population. Farmers .no resource poor and face tremendous constraints in gaining access to information and knowledge that t.ould improve their livelihoods. Even though farmers have the aspiration and potential to pursue further "ducation on new approaches, skills and techniques development has been negligible due to lack of opportunities and other constraints. Open and distance learning with appropriate information and I'ommunication technologies serves as a means for effective transfer of knowledge, information and tochnology, while being engaged in their cultivations thereby enabling to apply the knowledge directly to improve their cultivations and products. University of Colombo Institute of Agro-technology and Rural Sciences was established in 2008 with a mandate of providing, promoting and developing higher education in Agro-technology and Rural Sciences fimong persons presently engaged in Agriculture and Agro-technology to uplift farming as a prestigious occupation. An On-line Diploma Programme in Agro-technology in the local language and in English was doveloped by the Institute to provide education to the farmers at their doorsteps. Content development nnd delivery of the programme were made possible through the facilities of Distance Education Modernization Project (DEMP) of the Ministry of Higher Education. Computer skills gained through orientation programme enabled the farmers to learn on-line. Learner performance improved with time. Extensive learner support was provided through by dedicated online tutors and mentors of the Institute. Quality was ensured through adherence to the quality standards developed by DEMP in partnership with Common Wealth of Learning (COL). The knowledge gained through the course is immediately applied in their cultivations. This is the first ever attempt by the university system in the country in providing an opportunity for the larming community to pursue further and higher education while being engaged in their cultivation and Iransforms themselves to professional agri-business men and improves their socioeconomic status.